2004
DOI: 10.1200/jco.2004.10.042
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Proliferation, Apoptosis, Defective DNA Mismatch Repair, and p53 Overexpression in Patients With Resected Dukes' B2 or C Colon Cancer

Abstract: This retrospective study indicates that Ki-67 and ploidy may have stronger prognostic impact on OS and DFS than other parameters investigated after adjusting for stage and tumor grade. Prospective studies to elucidate the mechanism and prognostic significance of these findings are necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
74
1
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(89 citation statements)
references
References 56 publications
10
74
1
4
Order By: Relevance
“…However, the prognostic role of the Ki-67-labelling index in colorectal carcinoma is still highly controversial and probably different from other solid neoplasms. In fact, recent observations document that a high Ki-67-labelling index is associated with better OS (Allegra et al, 2003) in both treated and untreated patients (Garrity et al, 2004), as reported in the current series (Table 2).…”
Section: >100supporting
confidence: 82%
“…However, the prognostic role of the Ki-67-labelling index in colorectal carcinoma is still highly controversial and probably different from other solid neoplasms. In fact, recent observations document that a high Ki-67-labelling index is associated with better OS (Allegra et al, 2003) in both treated and untreated patients (Garrity et al, 2004), as reported in the current series (Table 2).…”
Section: >100supporting
confidence: 82%
“…Regarding Ki-67, studies have shown that its immunohistochemical expression is not correlated with survival (12) . However, in contrast, Garrity et al (9) reported that this marker was significantly associated with increased survival.…”
Section: Discussionmentioning
confidence: 90%
“…This finding is in agreement with the results presented by Kim et al (16) , in a study on 542 patients. On the other hand, despite similar data for p53 and bcl-2, Garrity et al (9) presented a different result for Ki-67 and concluded that the latter marker was strongly associated with longer disease-free intervals.…”
Section: Discussionmentioning
confidence: 92%
“…Of particular interest, there was no association with any other clinicopathological characteristic, and in a multivariate analysis, MICA was shown along side tumor stage and extramural vascular invasion to be an independent marker of prognosis. Although markers of growth, apoptosis and tumor suppressor gene products have been shown to be associated with disease progression, [21][22][23][24] this is the first time that a molecule involved in immune recognition of tumors has been shown to be an independent marker of good prognosis in colorectal cancer patients. Of particular interest is the strong association between MICA expression and survival in TNM stage III patients.…”
Section: Discussionmentioning
confidence: 99%